Chemical composition and anticholinesterase inhibitory activity of the essential oil of Pseuduvaria macrophylla (Oliv.) Merr. from Malaysia. Issue 11 (3rd June 2021) - Salleh, Wan Mohd Nuzul Hakimi Wan; Khamis, Shamsul; Nafiah, Mohd Azlan; Abed, Salam Ahmed
Abstract: This study was designed to examine the chemical composition and anticholinesterase inhibitory activity of the essential oil of Pseuduvaria macrophylla (Oliv.) Merr. (Annonaceae) from Malaysia. The essential oil was obtained by hydrodistillation and fully analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). The analysis led to the identification of thirty-four chemical components that represented 87.7 ± 0.5% of the total oil. The essential oil was found to be rich in germacrene D (21.1 ± 0.4%), bicyclogermacrene (10.5 ± 0.5%), δ-cadinene (5.6 ± 0.2%), α-copaene (5.1 ± 0.3%), and α-cadinol (5.0 ± 0.3%). Anticholinesterase activity was evaluated using Ellman method. The essential oil showed weak inhibitory activity against acetylcholinesterase (I%: 32.5%) and butyrylcholinesterase (I%: 35.4%) assays. Our findings demonstrate that the essential oil could be very useful for the characterization, pharmaceutical and therapeutic applications of the essential oil from Pseuduvaria macrophylla. Graphical Abstract: UF0001